SEM VDICENDI QUE]: AN ADDITIVE SUBORDINATIVE CONNECTIVE FROM PORTUGUESE (PERcursos Linguísticos, 2022)
This paper aims to describe the use and investigate the origin of [sem Vdicendi que], an additive connective that acts on attached and/or unattached clauses. The particular interest in this object is associated to: a) the lack of description of the object in the linguistic literature, despite its high frequency; b) the fact that it is a non-compositional subscheme of Portuguese, which probably suffered bleaching in relation to the negative modal/conditional construction, its probable origin. We base our analyzes on the theoretical assumptions of Usage-Based Linguistics (cf. CUNHA et al., 2013; OLIVEIRA & ROSÁRIO, 2016 etc.), with a special focus on the perspective of constructionality (AUTHOR, 2019), which allows us to hypothetically rebuild the diachronic trajectory of constructions based on their synchronic gradience.  A total of 248 tokens of the sequence of words sem + Vdicendi que were selected from Corpus Now (www.corpusdoportugues.org). The results show that this sequence of words can instantiate more than one construction: the hypotactic additive construction [sem Vdicendi que] and the modal/conditional construction [[sem][nonfinite clause]]. We argue that the additive construction has its origin in the modal/conditional one, given the fact that it is less compositional and its elements are more coalesced to each other.KEYWORDS: additive connective; attached and unattached clauses; constructionality; Usage-Based Linguistics.